A Case Study of the Effects of Posttraumatic Stress Disorder on Operational Fire Service Personnel Within the Lancashire Fire and Rescue Service - Khalid Khan; Jonathan Charters; Tony L. Graham; Hamid R. Nasriani; Shephard Ndlovu; Jianqiang Mai (Elsevier, 2018)
Background: Lancashire Fire and Rescue Service (LFRS), the subject of this evaluative research document employs 1400 people. 80% of employees are operational firefighters and officers whom operate across a range of duty systems and support functions, providing prevention, protection and emergency response to the communities of Lancashire. Methods: The overarching purpose of this epidemiological study is to assess the prevalence of post-traumatic stress disorder (PTSD) amongst operational LFRS personnel and to analyse the effects upon those who may be suffering from it, whether brought about by a single traumatic event or by repeated exposure to traumatic occurrences over a period of time. A combination of primary and secondary research was carried out. Primary data was collated using two recognised clinical questionnaires and statistical analysis was conducted with the aid of the software package SPSS. Results: The findings and statistical analysis showed that out of the 100 people surveyed, 30% of respondents had signs of probable distress. Of this quota, 4% showed symptoms of PTSD. The study considers how an organisation can recognise and manage PTSD and provides recommendations to assist in better recognising and managing the associated risks. Conclusion: Based upon the findings, the authors conclude that the level of PTSD within LFRS is slightly lower than those found in other studies undertaken within the Fire and Rescue Service sector. The paper provides recommendations for future studies and a series of actions for consideration by LFRS senior management to improve PTSD support services for employees. Keywords: Firefighters, Lancashire Fire and Rescue Service, Post-traumatic stress disorder, Survey, Trauma